Defendant’s Witness-Summoning Cost Budgeting by Public Prosecutors - Novritsar Hasintongan Pakpahan; Binsar Pamopo Pakpahan (Yayasan Cerdas Pedia Indonesia, 2026)
The Indonesian Criminal Procedural Law 2025 fundamentally alters trial dynamics, notably through Article 210, which imposes a new legal mandate on Public Prosecutors to formally summon the defendant’s witnesses. This normative legal research examines the implications of this obligation against the backdrop of insufficient financial allocations within the prosecution service. Utilizing statute, conceptual, and comparative approaches, this study identifies a critical budgetary vacuum that impedes prosecutorial duties and fundamentally undermines the principle of a fair trial. Findings indicate that while the burden of proof logically necessitates both parties to secure their respective witnesses, the current statutory framework forces prosecutors to bear this administrative responsibility. To resolve this predicament, the Public Prosecutor’s Office must enact specific internal regulations to restructure its financial framework. This restructuring must strictly allocate dedicated funds for summoning defense witnesses, clearly distinguishing between administrative summoning expenditures and actual attendance compensation, thereby ensuring continuous and equitable criminal proceedings.